2020
DOI: 10.14202/vetworld.2020.96-103
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization and phylogenetic study of Indonesian indigenous catfish based on mitochondrial cytochrome B gene

Abstract: Aim: This study aimed to determine the genetic characterization and phylogenetic structure of Indonesian indigenous catfish using cytochrome B (Cyt B) sequences. Materials and Methods: The genomes of 26 catfishes caught from nine rivers from nine different geographical locations around Indonesia were analyzed. The tissue isolation method was used to isolate the total genome of the fishes. Furthermore, polymerase chain reaction was done to amplify the mtDNA Cyt B using the CytBF and CytBR primers. Foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…This study supports the utility of the cytochrome b gene in phylogenetic relationships between Kryptopterus, Ompok, and Phalacronotus. This is in accordance with the results of molecular phylogenetic research that has been carried out on various species in the genus Puntius (Pallavi et al 2012), Pangasiidae and Schilbidae (Karinthanyakit and Jondeung 2012) and also catfish species in the family of Bagridae, Pangasiidae, and Ariidae (Megarani et al 2020).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This study supports the utility of the cytochrome b gene in phylogenetic relationships between Kryptopterus, Ompok, and Phalacronotus. This is in accordance with the results of molecular phylogenetic research that has been carried out on various species in the genus Puntius (Pallavi et al 2012), Pangasiidae and Schilbidae (Karinthanyakit and Jondeung 2012) and also catfish species in the family of Bagridae, Pangasiidae, and Ariidae (Megarani et al 2020).…”
Section: Resultssupporting
confidence: 90%
“…The research on cytochrome b in Indonesia has been carried out on Chanos chanos (Adiputra et al 2011), Puntius cf. binotatus (Karlina et al 2016), Osphronemus goramy (Nugroho et al 2019), Bagridae, Pangasiidae and Ariidae (Megarani et al 2020). Research on the cytochrome b gene in silurid catfishes is very scarce in Indonesia; in fact, cytochrome b data for O. eugeneiatus and O. hypophthalmus have not been in GenBank until now (updated on December 9 th of 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this research, samples from Bengawan Solo River, Bojonegoro, East Java and from Elo River, Magelang, Central Java had high number of nucleotides differences as well as the amino acid variation. These results supported the confirmation that the samples were different species based on cytochrome-B and cytochrome oxidase subunit III gene (Widayanti et al 2019;Megarani et al 2020) whereas samples from the Progo River, Magelang, Central Java were less different and closer to the samples from other rivers from the different islands. These results strengthen the hypothesis that distinguishes the species based on morphological features is not fully accurate so that geneticbased identification is needed.…”
Section: Variation Of Nucleotides and Amino Acids Sequencessupporting
confidence: 78%
“…Previous studies reported that geographical aspects in Indonesian lands influenced the speciation of catfish and resulted in genetic diversity of catfishes based on cytochrome-B and cytochrome oxidase subunit II gene (Widayanti et al 2019;Megarani et al 2020). Based on the previous reports, phylogenetic analysis using the DNA sequences is needed to reveal accurate species identification and support the conservation program.…”
Section: Variation Of Nucleotides and Amino Acids Sequencesmentioning
confidence: 99%
See 1 more Smart Citation